A biotechnological roadmap for decarbonization systems combined into bioenergy production: Prelude of environmental life-cycle assessment. (July 2023) - Yaashikaa, P.R.; Senthil Kumar, P.; Saravanan, A.; Karishma, S.; Rangasamy, Gayathri
Abstract: Decarbonization has become a critical issue in recent years due to rising energy demands and diminishing oil resources. Decarbonization systems based on biotechnology have proven to be a cost-effective and environmentally benign technique of lowering carbon emissions. Bioenergy generation is an environmentally friendly technique for mitigating climate change in the energy industry, and it is predicted to play an important role in lowering global carbon emissions. This review essentially provides a new perspective on the unique biotechnological approaches and strategies based decarbonization pathways. Furthermore, the application of genetically engineered microbes in CO2 biomitigation and energy generation is particularly emphasized. The production of biohydrogen and biomethane via anaerobic digestion techniques has been highlighted in the perspective. In this review, role of microorganisms in bioconversion of CO2 into different types of bioproducts such as biochemical, biopolymers, biosolvents and biosurfactant was summarized. The current analysis, which includes an in-depth discussion of a biotechnology-based roadmap for the bioeconomy, provides a clear picture of sustainability, forthcoming challenges, and perspectives. Graphical abstract: Image 1 Highlights: Role of biotechnology in decarbonization systems has been discussed in detail. Application of genetically modified micro-organisms for CO2 decarbonization is described. Bioenergy and bio-compounds generation coupled with decarbonization was critically explained. Sustainability of CO2 conversion to bioproducts and bioenergy in bio-based economy was discussed.